KARAKTERISTIK ARANG AKTIF DARI TEMPURUNG KELAPA DENGAN PENGAKTIVASI H2SO4 VARIASI SUHU DAN WAKTU - Siti Jamilatun; Siti Salamah; Intan Dwi Isparulita (Universitas Ahmad Dahlan, 2016)
Activated charcoal is charcoal that has been activated for increasing its surface area by opening the pores so increases the adsorption power. The surface area of the activated charcoal is between 300 and 3500 m2/g. Adsorption power from activated charcoal is very large, i.e. ¼ to 10 times the weight of activated charcoal. Activated charcoal is a good adsorbent for the adsorption of gases, liquids, and solutions. Characteristics of activated charcoal are moisture content, ash content, and absorption of the iodine. Manufacture of activated charcoal begins with soaking for 24 hours using 2N H2SO4 solution after it was drained and then roasted to remove the remaining water. Moisture content test was done by weighing 1 gram of activated charcoal and then put it in the oven at 105-1100C temperature for 120 minutes. Ash content test was by weighing 1 gram of activated charcoal and put in the furnace at a temperature of 5000C for 30 minutes, raise the temperature to 8150C for 90 minutes. Determination of the absorption of iodine is to weigh approximately 0.5 grams of activated charcoal and mix it with 50 ml of iodine solution 0.1 N. Shake it for 15 minutes. Take 10 ml of the sample solution and titrate with natrium thiosulfate solution 0.1 N. Adding amylum solution of 1% as an indicator to the titration result becomes colorless.This research produced the optimum conditions of oven temperature 10000C for 60 minutes. Activated charcoal obtained under these conditions has a good adsorption capability with high levels of iodine absorption of 529.94 mg I2/g charcoal.